APPLYING COOPERATIVE LEARNING BY A.L.A.M (AMATI, LAKUKAN, ANALISIS, MENGKREASI) TO STUDENTS LEARNING OUTCOMES ON JUNIOR HIGH SCHOOL - Muhammad Mudlir (INSECTA: Integrative Science Education and Teaching Activity Journal, 2022)
The background of this research was the low student learning outcomes in science material, especially the concepts of vibration and waves. This research aims to improve the learning outcomes of students in Junior High School through the using of A.L.A.M (Amati, Lakukan, Analisis, Mengkreasi). cooperative learning model.  This research is a Classroom Action Research where researchers work with physics teachers as observers. The research subjects were 32 students of class VIII A at State Junior High School, Merakurak Tuban. The techniques used in data collection are observation and tests. The data analysis technique used is quantitative descriptive analysis to analyze the results of the final test of each cycle and qualitative descriptive analysis to observe the results of each cycle. The research was carried out in 2 cycles and each cycle was carried out in 2 actions. The results showed that using of A.L.A.M cooperative learning model in science learning could improve student learning outcomes. This is indicated by an increasing in the value of student learning outcomes in pre-cycle to cycle II. In cycle, I, the average score obtained by students was 71.88 while in cycle II, the average value obtained by students reached 73.59. In conclusion, the using of A.L.A.M cooperative learning model (Amati, Lakukan, Analisis, Mengkreasi) can improve the learning outcomes of students.